The Causality of Qatar, Kuwait, and the United Arab Emirates Sharia Stock Indices on Indonesian Sharia Stock Index - Anisah Firli; Satria Jayasena (Budapest International Research and Critics University, 2021)
The capital market plays an important role in encouraging the investment, economy, and prosperity of a country. The sharia capital market was formed to be a new alternative in investing. The movement of the capital market can be influenced by various factors, one of which is the influence of other countries, also known as contagion, which in turn causes causality between the stock indices of each country. This study was conducted to determine whether there was a causal relationship between the sharia stock indices of Qatar and Indonesia, between the sharia stock indices of Kuwait and Indonesia, and between sharia stock indices of the United Arab Emirates and Indonesia. Stock index data of QERI, FTFLKS, FTDKUS, and ISSI for 5 years were tested using the Stationarity Test and the Granger Causality Test to determine the quality between indices. This study provides different findings from other studies, showing no causality in the sharia stock indices of Qatar, Kuwait, and the United Arab Emirates on Indonesia. The findings of this study can be used as input for investors in determining their investment portfolio if they wish to invest in the sharia capital market.